Carrier-envelope phase stabilization of grating-based chirped-pulse amplifiers - Moon, Eric Wayne (Kansas State University, 2009)
In this research, the carrier-envelope phase (CE phase) evolution of the pulse train from a Kerr-lens mode-locked chirped-mirror dispersion compensated Ti:Sapphire laser oscillator was stabilized. The offset frequency corresponding to the rate of change of the CE phase was obtained by spectrally broadening the oscillator pulses in a photonic crystal fiber and interfering the f and 2f components. An offset frequency linewidth of 100 mHz was obtained and could be locked over several hours. The effect of path length drift in the interferometer used for CE phase stabilization of the laser oscillator was investigated. By stabilizing the path length drift, the interferometer noise was reduced by several orders of magnitude. The CE phase drift through a grating-based chirped-pulse multi-pass amplifier was investigated. Varying the grating separation by 1μm in the stretcher was found to cause a shift of 3.7 +/- 1.2 rad of the CE phase. The CE phase could be stabilized to within 160 mrad rms error by feedback controlling the grating separation. By locking the path length in the f-to-2f interferometer used to stabilize the CE phase of the oscillator pulses, the fast (>3 Hz) CE phase drift of the amplified laser pulses was reduced from 79 to 48 mrad. It was also found that the CE phase could be shifted and set to any value within a 2π range by changing the grating separation. Also, the CE phase could be continuously modulated within a 2π range while maintaining a relative phase error of 171 mrad. The CE phase shift of a grating-based compressor was found to be stabilized to 230 mrad rms. The effect of laser power fluctuation on the CE phase measurement was also investigated. It was found that a 1% fluctuation of the laser energy caused a 160 mrad error in the CE phase measurement. A two-step model is proposed to explain the phase-energy coupling in the CE phase measurement. The model explains the experimentally observed dependence of the group delay between the f and 2f pulses on the laser energy. Few-cycle pulses were CE phase stabilized to 134 mrad rms and were used to perform above-threshold ionization and high harmonic generation.
Keywords: Carrier-Envelope Phase; Few-Cycle Laser; High Power Laser; Femtosecond; f-to-2f Interferometry; Physics, Atomic (0748); Physics, Optics (0752)